Effects of probiotic bacteria on gastrointestinal motility in guinea-pig isolated tissue - Massi, Matteo (Baishideng Publishing Group Co., Limited, 2006)
AIM: To evaluate the intestinal motility changes evoked by 8 bacterial strains belonging to Bifidobacterium, Lactobacillus and Streptococcus genera within the probiotic preparation VSL#3. METHODS: Ileum and proximal colon segments isolated from guinea-pigs were used as a study model. Entire cells and cell fractions (cell debris, cell wall fraction, cytoplasmatic fraction, proteinaceous and non-proteinaceous cytoplasmatic components) of VSL#3 strains and, as controls, Escherichia coli, Salmonella aboni and Bacillus licheniformis were tested in this in vitro model. RESULTS: Among the bacterial cell fractions tested, only the cytoplasmatic fraction modified intestinal motility. Lactobacillus strains stimulated the contraction of ileum segment, whereas all probiotic strains tested induced proximal colon relaxation response. The non-proteinaceous cytoplasmatic components were responsible for the colon relaxation. CONCLUSION: The results obtained in this study suggest that the proximal colon relaxation activity showed by the probiotic bacteria could be one of the possible mechanisms of action by which probiotics exert their positive effects in regulating intestinal motility.